Customers Behaviour in Online Shopping - Agarwal, Varsha (IJARESM, 2022)
(Lutkevich , 2022), Online shopping is a type of e-commerce that enables customers to purchasethings directly from an individual via their smartphones. The key goal of this research paper“Customers behaviour in online purchasing” is to learn more about customer’s attitudes andbehaviours in relation to online shopping. The study is basically to determine howonline-shopping affects customers since there are currently very few studies that adequatelyexplain how consumers behave online. These studies typically focus on a wide range of variablesand use a variety of methodologies and theoretical underpinnings. Additionally, this study alsoaims to understand the demographics, frequency of online buying and the preferred product listsof online customers. The major goal of this study is to determine whether customers are satisfiedwith the services offered via online shopping, the payment methods and other factors involved inpersuading customer’s preferences. Thus, this study focuses on users' opinions on every facet ofonline shopping that might be used as suggestions in the future. To gather data, both primary and secondary data have been employed. For primary data a questionnaire survey was used to gather different perspectives. It was evident that the respondents are at ease with online shopping but are not completely impulsive: there are elements that influence them, but there are certain issues that they are dealing with. Additionally,for secondary data different articles related to consumer behaviour towards online shopping werecollected and then briefly analysed to view the buying patterns and reasons that influence them to shop online.
ISME
Keywords: E-commerce; online shopping; customer behaviour; theoretical underpinnings